2010
DOI: 10.1038/cdd.2010.48
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhibition of Drp1-mediated mitochondrial fission is critical for myogenic differentiation

Abstract: During myogenic differentiation the short mitochondria of myoblasts change into the extensively elongated network observed in myotubes. The functional relevance and the molecular mechanisms driving the formation of this mitochondrial network are unknown. We now show that mitochondrial elongation is required for myogenesis to occur and that this event depends on the cellular generation of nitric oxide (NO). Inhibition of NO synthesis in myogenic precursor cells leads to inhibition of mitochondrial elongation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 52 publications
5
114
0
Order By: Relevance
“…This study (13) elegantly demonstrated that, using a specific nitric oxide (NO) synthase inhibitor, inhibition of NO/cGMP pathway increased Drp1 GTPase activity, translocation, and binding to mitochondria, which was accompanied by downregulation of the key myogenic regulatory factors. These results suggest that NO-dependent inhibition of Drp1 is an important step during early myogenic differentiation, which is seemingly contradictory to our finding that inhibition of Drp1 activity impairs myogenic differentiation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This study (13) elegantly demonstrated that, using a specific nitric oxide (NO) synthase inhibitor, inhibition of NO/cGMP pathway increased Drp1 GTPase activity, translocation, and binding to mitochondria, which was accompanied by downregulation of the key myogenic regulatory factors. These results suggest that NO-dependent inhibition of Drp1 is an important step during early myogenic differentiation, which is seemingly contradictory to our finding that inhibition of Drp1 activity impairs myogenic differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, a recent study by De Palma et al (13) reported that enhanced Drp1 activity and the resultant excessive mitochondrial fragmentation delayed myogenic differentiation, especially in the early phase of differentiation (3-12 h in DM). This study (13) elegantly demonstrated that, using a specific nitric oxide (NO) synthase inhibitor, inhibition of NO/cGMP pathway increased Drp1 GTPase activity, translocation, and binding to mitochondria, which was accompanied by downregulation of the key myogenic regulatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cell culture and differentiation Primary myoblasts from WT newborn mice were prepared using a protocol adapted from De Palma et al (44). After hind limb muscle isolation, muscles were minced and digested for 1.5 hours in PBS containing 0.5 mg/ml collagenase (Sigma-Aldrich) and 3.5 mg/ml Dispase (Gibco).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it increases mitochondrial fragmentation and cell death in neurodegenerative diseases by its effects on dynaminrelated protein-1 (DRP1), which promotes mitochondrial fission (Cho et al 2009). Conversely, in myogenesis, NO ‱ promotes the fusion of mitochondria into an elongated network by inhibiting Drp1-mediated fission (De Palma et al 2010).…”
Section: :1mentioning
confidence: 99%